2022
DOI: 10.1371/journal.pone.0265950
|View full text |Cite
|
Sign up to set email alerts
|

Burden of oral cancer in Asia from 1990 to 2019: Estimates from the Global Burden of Disease 2019 study

Abstract: Background Oral cancer (OC) poses a threat to human health and imposes a heavy burden on countries. We assessed the burden imposed by OC on Asian nations from 1990 to 2019 based on gender and age. Methods We collected oral cancer data from the 2019 Global Burden of Disease study from 1990 to 2019 in 45 Asian countries and territories. Annual case data and age-standardised rates (ASRs) were used to investigate the incidence, mortality, and disability-adjusted life-years (DALYs) of OC based on age and gender f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“… 1 Oral cancer is endemic and causes a great burden in Southern Asia because of habitual betel quid use, cigarette smoking, and chewing tobacco consumption. 1 , 2 Surgical resection of the primary malignancy with/without neck dissection has long been regarded as the best approach. The invasive nature of this disease makes it difficult to determine the margins, especially the deep margin, and the undesirable consequences of close or positive margins are still not uncommon, accounting for 11%-63% close margins and 7%-27% positive margins.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Oral cancer is endemic and causes a great burden in Southern Asia because of habitual betel quid use, cigarette smoking, and chewing tobacco consumption. 1 , 2 Surgical resection of the primary malignancy with/without neck dissection has long been regarded as the best approach. The invasive nature of this disease makes it difficult to determine the margins, especially the deep margin, and the undesirable consequences of close or positive margins are still not uncommon, accounting for 11%-63% close margins and 7%-27% positive margins.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] High risk behaviors observed in South Asian and Southeast Asian cohorts have given rise to an increased prevalence of etiological conditions prevailing in cancers of the head and neck. [ 2 ] Given the popularity of the primary high risk behaviors such as smoking, alcohol consumption and betel quid chewing in these regions, the increased incidence of oral cancer is epidemiologically relevant. [ 3 , 4 ] According to Xia et al, [ 2 ] the greatest societal burden of oral cancer is observed in Pakistan, Taiwan, China, and India.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Given the popularity of the primary high risk behaviors such as smoking, alcohol consumption and betel quid chewing in these regions, the increased incidence of oral cancer is epidemiologically relevant. [ 3 , 4 ] According to Xia et al, [ 2 ] the greatest societal burden of oral cancer is observed in Pakistan, Taiwan, China, and India. Furthermore, the highest risk factor is attributed to cigarette smoking, followed closely by alcohol consumption and chewing tobacco.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trained health professionals could, in theory, favour early diagnosis and local control of the disease by triage [18,19]. However, this approach is costly, time-consuming, laborious and may have limited results if it is performed by inexperienced professionals [12,18].…”
Section: Introductionmentioning
confidence: 99%